Interlaboratory variability of HER2 fluorescence in situ hybridization testing in breast cancer: results of a multicenter proficiency-testing ring study in China - Rongxue Peng; Kuo Zhang; Guigao Lin; Jinming Li (Diagnostic Pathology)
Abstract Background Accurate detection of human epidermal growth factor receptor 2 (HER2) gene amplification via fluorescence in situ hybridization (FISH) is necessary to determine HER2 status. Although many attempts have been made to increase the consistency of the results, the actual situation still needs to be determined. To investigate the latest interlaboratory variability of HER2 FISH testing for breast cancer, a multicenter proficiency-testing ring study was conducted in China. Methods A total of ten samples, each exhibiting distinct HER2 signal patterns and genetic heterogeneity, were distributed to 169 laboratories for HER2 FISH analysis. Data comprising both the results of the tests and feedback from questionnaires were compiled for comprehensive evaluation. Results The overall agreement among the participating laboratories was substantial to almost perfect, with a Fleiss’ kappa value of 0.765–0.911. However, it is important to note that cases with characteristics of HER2 signals near the critical cutoff range or with genetic heterogeneity showed lower congruence, poorer reproducibility, and higher variability (Fleiss’ kappa: 0.582). Our questionnaire showed that 52.2% (86/168) of the participants did not perform validation after their operation procedures or interpretation criteria were updated, and 75.6% (121/160) of the participants did not establish standard interpretation procedures. Since these laboratories showed worse performance (P < 0.05), the lack of validation and interpretation procedures was speculated to be the possible underlying cause. Conclusions This study presents the latest landscape of interlaboratory variability and accuracy of HER2 FISH testing in China and highlights potential causes for the variability. Despite many years of effort, the standardization of HER2 status determination still has a long way to go.